Game-based learning in early childhood education: a systematic review and meta-analysis - Alotaibi, Manar S. (Frontiers in Psychology, 2024)
Game-based learning has gained popularity in recent years as a tool for enhancing learning outcomes in children. This approach uses games to teach various subjects and skills, promoting engagement, motivation, and fun. In early childhood education, game-based learning has the potential to promote cognitive, social, and emotional development. This systematic review and meta-analysis aim to summarize the existing literature on the effectiveness of game-based learning in early childhood education This systematic review and meta-analysis examine the effectiveness of game-based learning in early childhood education. The results show that game-based learning has a moderate to large effect on cognitive, social, emotional, motivation, and engagement outcomes. The findings suggest that game-based learning can be a promising tool for early childhood educators to promote children's learning and development. However, further research is needed to address the remaining gaps in the literature. The study's findings have implications for educators, policymakers, and game developers who aim to promote positive child development and enhance learning outcomes in early childhood education.